Alih Wahana Tradisi Pujan Kasanga dalam Visual Komik - Sukmawan, Sony; Izza, Siti Fitrohitul (Humanis, 2024)
Pujan Kasanga Tradition is an important ritual of Tengger people because of being a tradition instrument in actualizing consistency of life. The potential of oral literature tradition in Pujan Kasanga can be developed into an artwork through alih wahana activity. Alih Wahana is purposing to visualize Pujan Kasanga oral literature inside comic which can introduce local culture from Tengger people. Alih Wahana method made through four steps such as preparing, imagining, developing imagination and working. Alih Wahana process bring a visual comic containing multiculturalism depicted through the plot of ritual processing followed by all of Tengger people without discriminating background of religion, faith, and social status. Next, local identity looks from the traditional costume that figure wore, profession, anjangsana culture and the culture of gathering. Last, own unique of Pujan Kasanga as an important ritual has big value and philosophy for Tengger people delivered on the environment background of shared and gotong royong, social environment concern, and harmony of living.